Systematic review and meta-analysis of percutaneous nephrolithotomy in flank versus prone position - He, Qing; Xiong, Liqiang; Wei, Renbo; Fu, Lei; Zhou, Liang; Yuan, Renbin; Zhuo, Hui (BMC urology, 2024)
This systematic review and meta-analysis aimed to evaluate the efficiency and safety of percutaneous nephrolithotomy (PCNL) between flank position and prone position for the treatment of renal stones. PubMed, Embase, OVID, and Cochrane Library were comprehensively searched from their inception to Jul 2024. Randomized and nonrandomized trials evaluating renal calculi patients who underwent PCNL via flank position or prone position were included. Data extraction and quality assessment were conducted by two independent reviewers. The outcomes and complications of both groups were compared in this meta-analysis. This review involved five articles (554 patients). Specifically, four articles were randomized controlled trials, and the remaining publication was prospective cohort study. No significant difference was found in stone-free rate between the flank group and prone group after the PCNL procedure. Similarly, the percutaneous access time, operative time, and hospital stay of flank position had no significant difference compared with the prone group. There was no significant difference in the comparison of complication rates between the flank group and the prone group. Although further analysis indicated that patients in the prone position suffered more hemoglobin drop than the flank group, no significant difference was found in the hemorrhage and blood transfusion rates. Both surgical positions were appropriate for most PCNL procedures and had shown similar efficacy and safety. In practice, the optimal choice should be made according to the patients' conditions and urologists' acquaintance.